Factors Affecting the Rotary Table Torque in Workover Rigs - Wang, Jiawei; Shao, Jun; Zhang, Qi; Qin, Haowei (International Journal of Mechanical and Electrical Engineering, 2025)
This paper addresses the accuracy bottleneck in torque monitoring for workover rig rotary tables, presenting a systematic analysis of the dynamic composition of torque, static influencing factors, and the characteristics of dynamic inertia. By establishing a torque balance equation, the coupling mechanisms among pipe string friction, mechanical transmission losses, and inertial torque are quantitatively revealed. The study specifically investigates the nonlinear effects of well inclination, dogleg severity, and cuttings bed thickness on frictional torque, as well as the degradation patterns of mechanical transmission efficiency due to clutch wear and braking modes. The results indicate that significant reduction in frictional torque can be achieved by: controlling the well inclination within the applicable range for conventional directional wells, optimizing trajectory design to suppress bending stress in sections with high dogleg severity, and real-time regulation of drilling parameters to maintain a cuttings bed thickness of less than 5 mm. Concurrently, clutch wear must be strictly controlled within a 0.5 mm threshold, and electromagnetic braking mode can effectively suppress torque fluctuations and mitigate impact loads. This research provides a theoretical foundation and technical support for the development of high-robustness, non-contact torque monitoring systems.